2010
DOI: 10.1016/j.engfracmech.2010.03.031
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of factory-roof formation

Abstract: ABSTRACT. The investigated factory-roof (F-R

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 12 publications
0
12
0
Order By: Relevance
“…The related numerical analysis 36 revealed that such elements are located at crack front sites predominantly loaded in mode II. The related numerical analysis 36 revealed that such elements are located at crack front sites predominantly loaded in mode II.…”
Section: B a C K G R O U N Dmentioning
confidence: 99%
See 4 more Smart Citations
“…The related numerical analysis 36 revealed that such elements are located at crack front sites predominantly loaded in mode II. The related numerical analysis 36 revealed that such elements are located at crack front sites predominantly loaded in mode II.…”
Section: B a C K G R O U N Dmentioning
confidence: 99%
“…The extrinsic (shielding) mechanisms occur in the surrounding of the crack tip as contacts of fracture surfaces during the cyclic loading, usually called crack closure. [24][25][26] For pure geometrical reasons, therefore, the size of crack wake asperities in form of branches or factory-roofs reduces and completely vanishes in the very low-cycle fatigue regime. Hence, the resistance to fatigue crack growth consists of two components: effective and crack closure induced.…”
Section: B a C K G R O U N Dmentioning
confidence: 99%
See 3 more Smart Citations